2013
DOI: 10.1089/cell.2012.0094
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Improves the Development and Acetylation Levels of Cat–Cow Interspecies Cloned Embryos

Abstract: Abnormal epigenetic reprogramming, such as histone acetylation, might cause low efficiency of interspecies somatic cell nuclear transfer (iSCNT). This study was conducted to evaluate the effects of trichostatin A (TSA) on the developmental competence and histone acetylation of iSCNT embryos reconstructed from cat somatic cells and bovine cytoplasm. The iSCNT cat and parthenogenetic bovine embryos were treated with various concentrations of TSA (0, 25, 50, or 100 nM) for 24 h, respectively, following fusion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The present study showed that the high levels of acetylation on H3K9/18/23 were observed in the TSA‐treated iSCNT cat‐cow embryos either at the PN or two‐cell stage, which resembles the bovine IVF embryos in this study and is in agreement with previous studies in mouse IVF (H3K9), sheep IVF (H3K9), cat iSCNT/IVF (H3K9) and miniature pig SCNT/IVF (H3K18) (Hou et al ; Yamanaka et al ; Gómez et al ). The hyper‐acetylation at several lysine residues of histone (H3K9/18/23) by TSA within a limited time (PN to two‐cell stage) in the present study might promote the development to the blastocyst from an iSCNT cat‐cow embryo as we reported previously (Wittayarat et al ), because TSA would re‐establish the embryonic epigenetic characteristics and gene expression (Shi et al ; Wu et al ) for an easier entry of some essential transcriptional factors into the nucleosome to activate gene expression (Yamanaka et al ), stimulating more effective remodelling of the somatic chromatin (Rybouchkin et al ).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The present study showed that the high levels of acetylation on H3K9/18/23 were observed in the TSA‐treated iSCNT cat‐cow embryos either at the PN or two‐cell stage, which resembles the bovine IVF embryos in this study and is in agreement with previous studies in mouse IVF (H3K9), sheep IVF (H3K9), cat iSCNT/IVF (H3K9) and miniature pig SCNT/IVF (H3K18) (Hou et al ; Yamanaka et al ; Gómez et al ). The hyper‐acetylation at several lysine residues of histone (H3K9/18/23) by TSA within a limited time (PN to two‐cell stage) in the present study might promote the development to the blastocyst from an iSCNT cat‐cow embryo as we reported previously (Wittayarat et al ), because TSA would re‐establish the embryonic epigenetic characteristics and gene expression (Shi et al ; Wu et al ) for an easier entry of some essential transcriptional factors into the nucleosome to activate gene expression (Yamanaka et al ), stimulating more effective remodelling of the somatic chromatin (Rybouchkin et al ).…”
Section: Discussionsupporting
confidence: 69%
“…Immunofluorescence analysis was processed according to the protocol described in our previous study (Wittayarat et al ). The embryos at 2 h PF/PI, 6 h PF/PI, PN, two‐cell, four‐cell and eight‐cell stages from the 50 nmol/L TSA‐treated iSCNT, TSA‐untreated control iSCNT and IVF groups were subjected to H3K9/18/23 ac immunofluorescence analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a previous study has shown that acH3K9 in SCNT embryos was increased with TSA treatment and reached similar levels to that of the IVF embryos [15]. As for acH4K5, it is found at low levels in bovine cloned embryos and can also be enhanced by TSA treatment [16].…”
Section: Discussionmentioning
confidence: 71%